Testamentary sources in Bergamo during the second half of the XII century - Maria Teresa Brolis; Andrea Zonca (Reti Medievali Rivista, 2010)
The study is based on archival documents, accurately edited according to proper scientific criteria and in light of current literature. It comprises commentaries of the edited sources, including a brief historiographical and methodological introduction. The thread of the argument is provided by elements of the structure of the documents themselves. They are specifically analysed according to the perspectives of diplomatics, of the history of the testators' families, and of their social relationships and history of the political, religious, and charitable institutions of Bergamo in the XII century.